1988
DOI: 10.1099/0022-1317-69-8-1789
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Nucleotide Sequence of Potato Virus X and Its Homologies at the Amino Acid Level with Various Plus-stranded RNA Viruses

Abstract: SUMMARYDouble-stranded cDNA of potato virus X (PVX) genomic RNA has been cloned and sequenced. The sequence [6435 nucleotides excluding the poly(A) tract] revealed five open reading frames (ORFs) which were numbered one to five starting at the 5' terminus of the RNA. They encoded proteins of Mr 165588 (166K), 24622 (25K), 12 324 (12K), 7595 (SK) and 25 080 (coat protein), respectively. ORFs 1 and 2 were inphase coding regions. The ORF 1 product contained domains of homology with the tobacco mosaic virus 126K a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(136 citation statements)
references
References 36 publications
3
133
0
Order By: Relevance
“…Cockerham (1955) classi®ed different isolates of PVX into four groups based on phenotype to two endogenous resistance genes in potato. PVX-CP (group 2; Orman et al, 1990), PVX-X3 and PVX-UK3 (group 3;Huisman et al, 1988;Kavanagh et al, 1992), PVX-HB (group 4; Querci et al, 1993), and a Russian isolate that we have designated PVX-R (Skryabin et al, 1988) were compared to our isolate (Hemenway et al, 1988) denoted as PVX-WA. PVX-WA is likely to be a group 3 strain based on amino acid similarities, but has not been tested on the appropriate host plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cockerham (1955) classi®ed different isolates of PVX into four groups based on phenotype to two endogenous resistance genes in potato. PVX-CP (group 2; Orman et al, 1990), PVX-X3 and PVX-UK3 (group 3;Huisman et al, 1988;Kavanagh et al, 1992), PVX-HB (group 4; Querci et al, 1993), and a Russian isolate that we have designated PVX-R (Skryabin et al, 1988) were compared to our isolate (Hemenway et al, 1988) denoted as PVX-WA. PVX-WA is likely to be a group 3 strain based on amino acid similarities, but has not been tested on the appropriate host plants.…”
Section: Resultsmentioning
confidence: 99%
“…The capped and polyadenylated viral RNA is composed of an 84 nt 5 H non-translated region (NTR), ®ve open reading frames (ORFs), and a 72 nt 3 H NTR (Huisman et al, 1988;Skryabin et al, 1988). ORF1 encodes the viral replicase protein, which is the only viral protein absolutely required for PVX RNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The viral genome consists of one single-stranded, positive sense RNA molecule with an estimated Mr of 2.4 × 106 which contains a T-terminal polyadenylated region. Recent nucleotide sequence data from PVS (MacKenzie et al, 1989) and a related carlavirus, potato virus M (PVM) (Rupasov et al, 1989), have demonstrated that these two viruses have genome organizations similar to that of potato virus X (PVX) (Huisman et al, 1988) and other members of the potexvirus group. The viral genome of PVS contains six open reading frames (ORFs) which encode polypeptides with Mr of 10734, 32515, 7222, 11802, 25092 and more than 41052.…”
Section: Potato Virus S (Pvs) Is a Member Of The Carlavirus Groupmentioning
confidence: 99%
“…On the basis of these properties, Scholthof (2004) classified this type of plant virus transport to the so-called Type II (see Table 1 Final ORF is virus capsid protein, engaged not only in assembling the particles but also in cell-to-cell transport (Huisman et al 1988;Santa Cruz et al 1998).…”
Section: Mp Tmv and Its Partners In Movementmentioning
confidence: 99%